COMPARATIVE ANALYSIS OF DOCTORAL STUDIES IN THE FIELD OF LAW: ROMANIA, BELGIUM AND LUXEMBOURG - Emilian MATEICIUC (Challenges of the Knowledge Society, 2025)
This study conducts a comparative analysis of doctoral education in the field of law across Romania, Belgium, and Luxembourg, exploring the structural, procedural, and institutional specificities that shape legal research training in these three EU Member States. Despite being part of the European Higher Education Area and adhering to the Bologna Process, the three countries display notable differences in the organization, funding, supervision, and evaluation of doctoral studies. The research adopts a qualitative, document-based methodology, focusing on national legislation, university regulations, and comparative literature to identify similarities and divergences across systems. The study examines critical areas including admission procedures, programme duration, supervisory frameworks, publication requirements, and thesis defence protocols. It underscores Romania’s more prescriptive regulatory approach, Belgium’s emphasis on academic autonomy and structured evaluation, and Luxembourg’s flexibility and strong international orientation. Particular attention is paid to the specific challenges facing Romanian institutions in aligning with Western European standards, especially regarding funding, research infrastructure, and academic visibility. Based on the comparative analysis, the paper outlines concrete measures to enhance quality assurance, promote internationalization, and ensure the integration of interdisciplinary and transferable skills in legal doctoral education. This comparative analysis contributes to the refinement of doctoral education policies in the EU, striking a balance between harmonisation and national academic traditions.